Vitamin D deficiency - a hidden culprit in dilated cardiomyopathy in children: a rare case report and review - Bainade, Kapil; Kotrashetti, Veeranna; Gahlowt, Pallavi; Nandikol, Shreya S. (International Journal of Contemporary Pediatrics, 2025)
Vitamin D deficiency (VDD) is a significant public health concern in India, especially in infants and children. Hypocalcemia originating from VDD is a cause of dilated cardiomyopathy (DCM). Here, we reported a case of a 4-month-old infant who was diagnosed with DCM secondary to hypocalcemia-associated VDD. A 4-month-old full-term female infant presented to the emergency with three episodes of apneic spells and a feeding history of improperly prepared formula and diluted cow’s milk with no other supplementation. The baby had normal vitals and no abnormal examination findings. Investigations revealed severe hypocalcemia with prolonged QTc interval on electrocardiogram. Further investigations showed VDD, and echocardiography showed DCM with mild left ventricular dysfunction. The infant was managed with calcium and mega doses of vitamin D. There was DCM resolution and ventricular function improvement. The infant was discharged with no morbiditiesn. Despite its importance, VDD persists as a significant public health challenge in Indian infants and children, resulting from a complex interplay of factors. Hypocalcemia due to VDD results in a form of reversible DCM, causing heart failure. Consistent with our case, numerous published case series have demonstrated that infants and children with VDD often present with cardiac dysfunction and DCM at various stages and show dramatic improvement following vitamin D supplementation. Dilated cardiomyopathy may be more common than previously thought as a complication of vitamin D deficiency, but early detection and timely intervention can lead to swift recovery.